Pokémon adventures. Diamond and Pearl platinum. 05 - Kusaka, Hidenori (Kusaka, Hidenori. Poketto monsutā supesharu. Diamond and Pearl platinum, 2012)
Pokémon trainers Pearl and Diamond have a lifelong dream to star in a Pokémon comedy act, but somehow end up as bodyguards to a pampered rich girl on a quest to reach the peak of Mount Coronet.